Sex difference in clinical and procedural outcomes in patients undergoing coronary atherectomy: a systematic review and meta-analysis. Issue 8 (17th October 2022) - Thandra, Abhishek; Pajjuru, Venkat; Jhand, Aravdeep; Ponamgi, Shiva; Ismayl, Mahmoud; Torres, Rosa Cruz; Sharma, Arunima; Narmi, Ann; Agarwal, Himanshu; Kanmanthareddy, Arun
Abstract : Background: Rotational and orbital coronary atherectomy (CA) are commonly utilized to treat complex calcified coronary lesions. We conducted a meta-analysis to evaluate sex differences in procedural complications and clinical outcomes after CA. Methods: PubMed, Google Scholar, and Cochrane databases were searched for all studies comparing sex differences in procedural and clinical outcomes following CA. The outcomes of interest were procedural complications (coronary dissection, stroke, major bleeding, coronary perforation, cardiac tamponade, and slow or no flow in target vessel) and the clinical outcomes (including early mortality, mid-term all-cause mortality, stroke, myocardial infarction, and target vessel revascularization). Pooled risk ratios (RRs) with their corresponding 95% confidence intervals (CIs) were calculated using the Mantel–Haenszel random-effects model. Results: Six observational studies with 3517 patients (2420 men and 1035 women) were included in this meta-analysis. While there was no significant difference in the early mortality (RR, 1.14; 95% CI, 0.37–3.53; P = 0.83) between men and women, at a mean follow-up of 2.9 years, all-cause mortality was significantly higher in women (RR, 1.29; 95% CI, 1.11–1.49; P = 0.0009). Women had an increased risk of procedure-related stroke (RR, 3.98; 95% CI, 1.06–14.90; P = 0.04), coronary dissection (RR, 2.10; 95% CI, 1.23–3.58; P = 0.006), and bleeding (RR, 2.26; 95% CI, 1.30–3.93; P = 0.004), whereas the rates of coronary perforation, cardiac tamponade, and the risk of slow or no flow in the revascularized artery were similar in both. Conclusion: In our analysis, women undergoing CA are at increased risk of mid-term mortality and procedure-related complications including stroke, coronary dissection, and major bleeding.